Different Effects of Thermophilic Microbiological Inoculation With and Without Biochar on Physicochemical Characteristics and Bacterial Communities in Pig Manure Composting - Sun, Likun; Long, Min; Li, Jianshu; Wu, Renfei; Ma, Lin; Tang, Defu; Lu, Yongli; Wang, Ziyu (Frontiers in Microbiology, 2021)
This study evaluated the effects of thermophilic microbiological inoculation alone (TA) and integrated with biochar (TB) on the physicochemical characteristics and bacterial communities in pig manure (PM) composting with wheat straw. Both TA and TB accelerated the rate of temperature increase during the PM composting. TA significantly reduced total nitrogen loss by 18.03% as opposed to TB which significantly accelerated total organic carbon degradation by 12.21% compared with the control. Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria were the major phyla in composting. Variation of the relative abundance of genera depended on the composting period and treatment. The genera Lactobacillus (26.88–46.71%) and Clostridium_sensu_stricto (9.03–31.69%) occupied a superior position in the temperature rise stage, and Bacillus (30.90–36.19%) was outstanding in the cooling stage. Temperature, total nitrogen (TN), and ammonium nitrogen significantly influenced the bacterial phyla composition. TN, water content, and nitrite nitrogen were the main drivers of the bacterial community genera. Furthermore, our results demonstrated that microbiological consortia were resistant to high temperatures and could fix nitrogen for enriched Pseudomonas; however, when interacted with biochar, total organic carbon (TOC) degradation was accelerated for higher bacterial richness and diversity as well as overrepresented Corynebacterium.